The Effect of Motivation and Discipline on Employee Performance Primary Bookshop - Nurhayati Nurhayati; Noor Muhammadi; Noor Permadi; Taufiqurrachman Taufiqurrachman (Jurnal Mantik, 2022)
To face business competition with similar business competitors, Pratama Bookstores must have competent human resources to improve the quality of running their business. This study aims to determine the effect of work motivation and work discipline on the performance of Pratama Bookstore employees. This type of research uses quantitative associative methods using multiple linear regression analysis techniques. The population and sample in this study were all employees of the sales division of the Pratama Bookstore, totaling 35 employees. The sampling decision-making technique in this research is non-probability sampling with saturated sampling method. The results of this study indicate that partially the work motivation variable has a positive and significant effect on employee performance, and the work discipline variable has a positive and significant effect on employee performance. When viewed from the results of the coefficient of determination, it is obtained that 73.9% of employee performance is influenced by work motivation and work discipline, while the remaining 26.1% is influenced by variations in other variables not included in this study.